Women and economics: New historical perspectives - Cléo Chassonnery-Zaïgouche; Evelyn L. Forget; John D. Singleton (Duke University, Center for the History of Political Economy (CHOPE), 2022)
This essay is the introduction to the History of Political Economy Annual Supplement on 'Women and Economics: New Historical Perspectives.' We first reflect on the historiography of economics and the relative absence of women and gender in the mainstream of the field. Three approaches to the history of women and economics are delineated: making visible women economists, outlining the impact of including women in a broader narrative about economics, and analyzing gender metaphors in economic thought. We then preview and describe the nine contributions included in the volume. In the last of section, we consider 'what's next' for this research agenda, arguing that there are two important challenges to historians of economics. The first challenge concerns the consequences of delegating women and gender to a separate history. The second challenge concerns the 'silences' of unwritten, un-developed, and un-preserved work in the history of economics and how the community engaged with the past of economics should reflect on these.
Keywords: 330; Wirtschaftswissenschaft; Ökonomen; Geschlecht